PENGETAHUAN, SIKAP, DAN PRAKTEK ASI EKSLUSIF SERTA STATUS GIZI BAYI USIA 4-12 BULAN DI PEDESAAN DAN PERKOTAAN - Asrinisa Rachmadewi; Ali Khomsan (Jurnal Gizi dan Pangan, 2009)
The main aim of this study was to compare breastfeeding knowledge, attitude, and practice and infants nutritional status between rural and urban areas. In this cross-sectional study, Desa Jayabakti, Kabupaten Sukabumi represents rural area, while Kelurahan Kedung Jaya, Kota Bogor represents urban area. Samples were 31 mothers-infants in each area who were selected by simple cluster sampling method. The differences between two areas were analyzed with the independent t-test, chi-square test, and Fisher's exact test. The correlation between variables was analyzed with rank Spearman. The result of this study showed that mother's knowledge and attitude of nutrition, especially about exclusive breastfeeding, was higher in urban than in rural area. There were differences in mothers' knowledge and attitude between rural and urban areas (p<0.05). Exclusive breastfeeding in rural area practiced by 41.9%, which is higher than in urban area (25.8%). Nevertheless, there was no statistical difference in exclusive breastfeeding practice between rural and urban areas (p>0.05). The aspects of breastfeeding practices which statistically difference in rural and urban areas were the introduction of colostrums status and breastfeeding time (p<0.05). Early initiation of breastfeeding was associated with exclusive breastfeeding practice in urban area (p<0.05), but none of the variables were associated with exclusive breastfeeding practice in rural area (p>0.05). Furthermore, exclusive breastfeeding practice was not associated with 4-12 months infants nutritional status (p>0.05). Mothers' family should be targeted as target of audience in breastfeeding promotion.  Keywords: breastfeeding practice, exclusive breastfeeding, knowledge, attitude, infant                  nutritional status, rural and urban areas.